Evaluating qigong as integrative support for COVID-19 and Long-COVID-19 rehabilitation: a systematic review - Antonelli, Michele; Donelli, Davide (Frontiers in Psychology, 2024)
Amidst the ongoing global impact of COVID-19 on public health, there is an increasing focus on holistic strategies encompassing integrative therapies and rehabilitation techniques, particularly in addressing the challenges posed by Long-COVID-19. This review investigates the potential of Qigong, an ancient Chinese practice characterized by gentle movements, controlled breathing, and meditative elements, within the context of COVID-19. A systematic search of PubMed, EMBASE, Web of Science, Scopus, and Google Scholar was conducted to identify pertinent clinical studies. Following thorough database scrutiny, nine studies were identified as meeting the eligibility criteria. Across the spectrum of COVID-19 severity, individuals engaging in qigong practice exhibited notable enhancements in both physical and psychological well-being, evidenced by ameliorated respiratory symptoms, reduced anxiety levels, enhanced sleep quality, bolstered mental well-being, and augmented health-related quality of life. Moreover, qigong training, whether employed independently or in conjunction with other therapies, demonstrated beneficial effects on Long-COVID-19 symptoms, encompassing persistent respiratory issues, dizziness, sleep disturbances, and compromised health-related quality of life. This review underscores the necessity for further investigation to quantify and standardize the contribution of Qigong to COVID-19 recovery and rehabilitation. Such endeavors aim to integrate this accessible and low-impact practice into public health strategies and comprehensive treatment regimens.